Análisis jurídico social del numeral 2 del artículo 528 del código penal ecuatoriano referente a la pena de la práctica del proxenetismo y corrupción de menores realizada en la ciudad de Machala, periodo 2011- 2012 propuesta reforma jurídica penal. - Bustamante Mato, Guido Jhobany (2012)
In this scientific work, is reflected in all the research that has done, giving a look at the reality from a clear and concrete perspective of what happens with our group more vulnerable especially the girls and adolescents, where the social and legal gaps Give more than an open field for this type of abuse.